2008
DOI: 10.1152/japplphysiol.01272.2007
|View full text |Cite
|
Sign up to set email alerts
|

(Over)training effects on quantitative electromyography and muscle enzyme activities in standardbred horses

Abstract: To study whether quantitative needle electromyography (QEMG) is more sensitive to detect training (mal)adaptation than muscle enzyme activities, 12 standardbred geldings trained for 32 wk in age-, breed-, and sex-matched fixed pairs. After a habituation and normal training (NT) phase (phases 1 and 2, 4 and 18 wk, respectively), with increasing intensity and duration and frequency of training sessions, an intensified training (IT) group (phase 3, 6 wk) and a control group (which continued training as in the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
4
15
1
Order By: Relevance
“…In a recent study it was shown that exercise positively influences hypertrophy and neuromuscular excitability in humans and horses (Mileva et al, 2010;Wijnberg et al, 2008). Indeed, both of these authors found an increase in amplitude with exercise, a finding that is in agreement with the present study (see Figure 2).…”
Section: Exercise and The Semg Signalsupporting
confidence: 93%
See 1 more Smart Citation
“…In a recent study it was shown that exercise positively influences hypertrophy and neuromuscular excitability in humans and horses (Mileva et al, 2010;Wijnberg et al, 2008). Indeed, both of these authors found an increase in amplitude with exercise, a finding that is in agreement with the present study (see Figure 2).…”
Section: Exercise and The Semg Signalsupporting
confidence: 93%
“…The short yet coordinated bursts of sEMG signal activity in the HW horses in the present study reflects a training induced synchronization of the individual compound muscle action potentials (CMAPs) within the UL muscle measured (Mileva et al, 2010;Wijnberg et al, 2008).…”
Section: Exercise and The Semg Signalmentioning
confidence: 59%
“…The increases in number of turns in HNP4 and HNP7 and duration in HNP7, suggest a less synchronous arrival of the individual motor unit action potentials of which the recorded motor unit action potential is composed (Gabriel et al . 2006; Wijnberg et al . 2008), which is in agreement with the results of the single fibre EMG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition training adaptation can also be elucidated using this technique (Gabriel et al . 2006; Wijnberg et al . 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation